Vital Signs Directed Therapy for the Critically Ill: Improved Adherence to the Treatment Protocol Two Years after Implementation in an Intensive Care Unit in Tanzania. (7th January 2020) - Hvarfner, Anna; Blixt, Jonas; Schell, Carl Otto; Castegren, Markus; Lugazia, Edwin R.; Mulungu, Moses; Litorp, Helena; Baker, Tim
Abstract : Treating deranged vital signs is a mainstay of critical care throughout the world. In an ICU in a university hospital in Tanzania, the implementation of the Vital Signs Directed Therapy Protocol in 2014 led to an increase in acute treatments for deranged vital signs. The mortality rate for hypotensive patients decreased from 92% to 69%. In this study, the aim was to investigate the sustainability of the implementation two years later. An observational, patient-record-based study was conducted in the ICU in August 2016. Data on deranged vital signs and acute treatments were extracted from the patients' charts. Adherence to the protocol, defined as an acute treatment in the same or subsequent hour following a deranged vital sign, was calculated and compared with before and immediately after implementation. Two-hundred and eighty-nine deranged vital signs were included. Adherence was 29.8% two years after implementation, compared with 16.6% (p < 0.001 ) immediately after implementation and 2.9% (p < 0.001 ) before implementation. Consequently, the implementation of the Vital Signs Directed Therapy Protocol appears to have led to a sustainable increase in the treatment of deranged vital signs. The protocol may have potential to improve patient safety in other settings where critically ill patients are managed.